G85(P) Follow up of asymptomatic microscopic haematuria/proteinuria – different perspectives of paediatric emergency medicine, general paediatrics and paediatric nephrology. (27th April 2015) - Hastings, RA; Surridge, J; Lunn, AJ
Abstract : Aims: To examine the practice of different sub-specialists with regard to the follow up of microscopic haematuria/proteinuria as an incidental finding in febrile children. Methods: Data from an online survey of responses to hypothetical scenarios of febrile children with incidental findings of microscopic haematuria/proteinuria in children with no overt signs of renal disease was collected. The survey was sent to registrars and consultants in paediatric emergency medicine, in paediatric nephrology and in general paediatrics. It asked for the doctors' current practice in arranging follow up of children with positive urine dipstick results. Results: A response to the survey was obtained from 34 paediatric emergency medicine (PEM) specialists, 10 paediatric nephrologists (PN) and 19 general paediatricians (PG). Table 1 shows the current practice of these doctors in managing children with 1+ positive urine dipstick (1+ P/H; either protein or blood) and with 3+ proteinuria and 3+ haematuria (3+P&H). Amongst consultants, PEM doctors were 3x more likely to investigate 3+ haematuria and proteinuria as inpatients when compared with renal consultants. These differences suggest a trend towards increased follow-up recommended by paediatric nephrologists but with fewer admissions which was not statistically significant (Pearson Chi squared test). Conclusions: An incidental finding of haematuria/proteinuria is common in CED. Approximately 2/3 of microscopic haematuria/proteinuria in children without specific renal symptoms resolves. Ensuring resolution is important since up to 50% of children in whom it persists have renal disease. 1 Here we show a trend for nephrologists to follow up more urine dipstick results but for PEM doctors to admit more children for inpatient investigations. PEM doctors and general paediatricians tend to have similar patterns of follow up. Reference: Geary DF, Schaefer F. Comprehensive Pediatric Nephrology. Philadelphia: Mosby, 2008